Gut Microbial Antigenic Mimicry in Autoimmunity - Garabatos, Nahir; Santamaria, Pere (Frontiers in Immunology, 2022)
The gut microbiota plays a major role in the developmental biology and homeostasis of cells belonging to the adaptive and innate arms of the immune system. Alterations in its composition, which are known to be regulated by both genetic and environmental factors, can either promote or suppress the pathogenic processes underlying the development of various autoimmune diseases, including inflammatory bowel disease, multiple sclerosis, systemic lupus erythematosus, type 1 diabetes and rheumatoid arthritis, to just name a few. Cross-recognition of gut microbial antigens by autoreactive T cells as well as gut microbe-driven alterations in the activation and homeostasis of effector and regulatory T cells have been implicated in this process. Here, we summarize our current understanding of the positive and negative associations between alterations in the composition of the gut microbiota and the development of various autoimmune disorders, with a special emphasis on antigenic mimicry.